REPOSITIONING CHRISTIAN EDUCATION IN THE AGE OF ARTIFICIAL INTELLIGENCE: AN ONTOLOGICAL-EPISTEMOLOGICAL DISCERNMENT FRAMEWORK - Desomon Ayub Adu; Hendra Nike Carter Bangun (Jurnal Suluh Pendidikan, 2026)
Christian religious education must consider the philosophical and theological implications of the penetration of artificial intelligence into learning practices. This study uses a meta-synthesis approach to identify how AI transforms ontology and epistemology in the context of Christian education. The literature review includes studies on the philosophical foundations of Christian education, the impact of AI on education in general, ontological-epistemological frameworks, and Christian discernment theory. Key findings indicate that AI can enhance personalized learning and enrich Christian content, but requires integration that aligns with Christian values ​​of love, truth, and justice. Therefore, an ontological-epistemological discernment framework is needed that emphasizes reflection on human nature as the image of God and knowledge based on divine revelation. This framework is outlined in curriculum recommendations and educational practices, such as teacher training on faith-guided AI literacy and adaptation of AI-Christian teaching materials. Limitations of this study include reliance on literature studies without empirical field data.